(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Urbanization is the process of transformation through which cities develop, and higher percentages of the population come to live in the city or urban area. Urbanization has a positive impact in the path of development. According to World Bank estimation, more than 80% of global GDP generates in cities. Urbanization can contribute to sustainable growth through increased productivity and innovation if managed well. During 2011 census, Assam has an urbanization rate of 14% approximate which is lower compared to 31% of national urbanization rate. This paper intends to study the trend of urbanization in Assam over the years and the rate of growth of urban population. It also seeks to study the impact of urbanization on socio economic development and environment. The findings show that there is an increasing trend in the rate of growth of urbanization. Proper management and planning is required to induce organised and sustainable economic development and to protect the environment from degradation.